KAJIAN FINANSIAL PENGADAAN PERALATAN PENGUKUR KETIDAKRATAAN JALAN LASER PROFILEMETER KELAS I HAWKEYE 2000 DI LINGKUNGAN BALAI PELAKSANAAN JALAN NASIONAL BENGKULU - Budiharto, Punto; Amanah, Tody (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2023)
Balai Pelaksanaan Jalan Nasional (BPJN) Bengkulu was born based on PUPR Regulation Number. 26 of2020. The Function is the implementation of feasibility studies, surveys, investigation, and evaluation ofplanning for the technical field of road and bridge including road safety. The Important type of survey arelongitudinal profile survey International Roughness Index (IRI), and Pavement Condition Index (PCI). TheMethod is to examined secondary data obtained from literature review and analyzed financial data (NetPresent Value, Benefit Cost Ratio, and Payback Period. The author builds four scenarios (pessimistic,medium, optimistic, and do nothing). The Benefit Cost Ratio for the scenario 1 (pessimist) is 0.33, thescenario 2 (medium) is 1.54, the scenario 3 (optimistic) is 2.82, and the scenario 4 (do-nothing) is N/A.Value of Payback Period for the scenario 2 (medium) is 5.62 years, and the scenario 3 (optimistic) is 2.79years. Based on the analysis, the decision to purchase a Hawkeye 2000 digital laser profilemeter withinBPJN Bengkulu is financially feasible as long as the hawkeye used not only for Internal, but as a source ofPNBP from client like private sector or provincial government, and distric or city governments in BengkuluProvince.